DAMPAK POLA ASUH PANTI ASUHAN PADA TINGKAH LAKU ANAK PANTI ASUHAN IBRAHIM SITUJUAH BATUA - Alyatul Hapzia; Linda Yarni (Pusat Riset dan Inovasi Nasional, 2023)
The problem in this study is the impact of orphanage parenting on the behavior of the children at the Ibrahim Situjuah Batua orphanage. Which parenting style is applied by the foster parents in the orphanage will have a major effect on a child's behavior because it is from the parenting style that the behavior will be maturely formed, both good behavior and bad behavior. The purpose of this study was to determine the parenting style of the orphanage on children's behavior. This study used a descriptive method with data collection techniques by means of observation and interviews. With the observation and interviews, the data obtained is clearer and more accurate.